Leveraging Blockchain for Enhanced Visibility and Sustainability in the Energy Sector Supply Chain - Zhang, Juan; Lin, Zeyu; Chen, Junpeng (International Journal of Electric Power and Energy Studies, 2024)
The energy sector faces significant challenges related to supply chain traceability, including issues with transparency, data integrity, regulatory compliance, and fraud prevention. Blockchain technology, with its decentralized, transparent, and immutable ledger, offers promising solutions to these challenges. This review explores the application of blockchain technology in enhancing supply chain traceability in the energy sector. It examines the potential benefits in terms of visibility, data integrity, compliance, and sustainability, and discusses real-world applications, challenges, and future directions. Case studies from renewable energy, fossil fuels, and smart grids illustrate blockchain's impact. Despite the promising benefits, technical, regulatory, and implementation challenges remain. Future research and development, along with supportive policy frameworks, are essential for realizing blockchain's full potential in transforming the energy supply chain into a more efficient, transparent, and sustainable system.